Dppa3 is critical for Lin28a-regulated ES cells naïve–primed state conversion. (27th November 2018) - Sang, Hui; Wang, Dan; Zhao, Shuang; Zhang, Jinxin; Zhang, Yan; Xu, Jia; Chen, Xiaoniao; Nie, Yan; Zhang, Kaiyue; Zhang, Shuaiqiang; Wang, Yuebing; Wang, Na; et al.
Abstract: Lin28a is a pluripotent factor that promotes somatic cell reprogramming. Unlike other pluripotent factors, Lin28a expression is transient and accumulated in primed embryonic stem (ES) cells, but its exact function and mechanism in the conversion of ES cells from naïve to primed state remain unclear. Here, we present evidence for Dppa3, a protein originally known for its role in germ cell development, as a downstream target of Lin28a in naïve–primed conversion. Using rescue experiment, we demonstrate that Dppa3 functions predominantly downstream of Lin28a during naïve–primed state conversion. Higher level of Lin28a prevents let-7 maturation and results in Dnmt3a/b (target of let-7) upregulation, which in turn induces hypermethylation of the Dppa3 promoter. Dppa3 demarcates naïve versus primed pluripotency states. These results emphasize that Lin28a plays an important role during the naïve–primed state conversion of ES cells, which is partially mediated by a Lin28a–let-7–Dnmt3a/b–Dppa3 axis.